PLK1-mediated phosphorylation of PPIL2 regulates HR via CtIP - Qiu, Zhiyu; Hao, Shuailin; Song, Shikai; Zhang, Ruiling; Yan, Tingyu; Lu, Zhifang; Wang, Hailong; Jia, Zongchao; Zheng, Jimin (Frontiers in Cell and Developmental Biology, 2022)
Homologous recombination (HR) is an error-free DNA double-strand break (DSB) repair pathway, which safeguards genome integrity and cell viability. Human C-terminal binding protein (CtBP)—interacting protein (CtIP) is a central regulator of the pathway which initiates the DNA end resection in HR. Ubiquitination modification of CtIP is known in some cases to control DNA resection and promote HR. However, it remains unclear how cells restrain CtIP activity in unstressed cells. We show that the ubiquitin E3 ligase PPIL2 is recruited to DNA damage sites through interactions with an HR-related protein ZNF830, implying PPIL2’s involvement in DNA repair. We found that PPIL2 interacts with and ubiquitinates CtIP at the K426 site, representing a hereunto unknown ubiquitination site. Ubiquitination of CtIP by PPIL2 suppresses HR and DNA resection. This inhibition of PPIL2 is also modulated by phosphorylation at multiple sites by PLK1, which reduces PPIL2 ubiquitination of CtIP. Our findings reveal new regulatory complexity in CtIP ubiquitination in DSB repair. We propose that the PPIL2-dependent CtIP ubiquitination prevents CtIP from interacting with DNA, thereby inhibiting HR.